Nucleotide sequence of the 3' half of AKV. - Herr, W (1982)
We report the nucleotide sequence of the 3' half of the ecotropic murine leukemia virus AKV genome. To obtain a preliminary sequence, we developed a sequencing strategy whereby a nested set of restriction fragments is chemically modified prior to gel purification and strand scission. The sequence defines the genetic map of the 3' half of AKV and locates recombinant regions previously identified in structural analyses of MCF viruses.